Text Worlds: A Cognitive-Stylistic Analysis of: A Passage to India - Dr. Nijat Ullah Khan,; Dr. Abdul Waheed Qureshi,; Aziz Ullah Khan,; Yousaf Kamran, (Al-Qanṭara, 2022)
This study examines the way a reader can infer meanings from the text by connecting language with the context in which it is produced. The text-world model is thus applied to the selected excerpts from the well-known novel A Passage to India by Edward M. Forster (2007), in order to investigate the extent to which discourse worlds, text worlds, and sub-worlds contribute to the development of mental representations. The study employs a qualitative-analytical research design. Moreover, Text World Theory (TWT) by Werth (1999) lends credence to the study. The investigation showed that TWT is the ideal framework for evaluating mental models in novels. The study also revealed that the amalgam of language and context produced a wide variety of social, intellectual, and cultural perspectives. The research will add to the body of knowledge collected through objective and cognitive stylistic analysis. Keywords: Context; Discourse; Meanings; Mental Constructs; Text World Theory (TWT)